Pengaruh Brand Image, Word of Mouth, dan Persepsi Harga terhadap Keputusan Konsumen Pembelian Produk Minyak Kutus-Kutus di Kota Denpasar - Siangan, Ida Bagus Gede Bajra; Sunia, I Wayan; Lestari, Ni Putu Nina Eka (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The growing competition in the herbal industry requires companies to strengthen their marketing strategies to maintain consumer loyalty. Kutus-Kutus Oil, a traditional herbal product in Denpasar, faces challenges in sustaining purchase decisions amid similar competing brands. This study aims to examine the influence of brand image, word of mouth, and price perception on consumer purchase decisions for Kutus-Kutus Oil in Denpasar City. The research employed a quantitative associative approach with 99 respondents selected using the Slovin formula. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 26. The results show that brand image, word of mouth, and price perception each have a positive and significant effect on consumer purchase decisions. Simultaneously, these three variables explain 63.7% of the variation in purchase decisions, indicating that consumer perception of brand strength, peer recommendations, and price fairness plays a key role in determining buying behavior. These findings suggest that enhancing brand credibility and managing online consumer engagement can strengthen the market position of local herbal products.